2018
DOI: 10.1111/tbj.13126
|View full text |Cite
|
Sign up to set email alerts
|

Secretory breast carcinoma in an 8-year-old girl: A case report and literature review

Abstract: Secretory breast carcinoma (SBC) is a rare form of breast cancer found in both children and adults, and is the most common breast cancer in the pediatric population.Although SBC usually carries a favorable prognosis, there have been reported cases of axillary and distant metastases. Surgery is the primary mode of treatment, however, there exists variability within the literature surrounding the management of SBC. We report a case of an 8-year-old girl who presented with a firm, mobile, palpable breast mass. Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 48 publications
0
27
0
2
Order By: Relevance
“…[39][40][41][42] In their review of the literature, Garlick et al found that of the 44 cases of secretory carcinoma of the breast wherein IHC for hormone receptors were performed, eight of 44 (18%) of cases were ER positive, six of whom were men. 22 The group found no apparent association with ER positivity and age, tumour size, metastases or clinical outcome in these cases. In their immunohistochemical and genomic review of secretory carcinoma of the breast and mammary analogue secretory carcinoma, Krings et al reported 44% of their SCB cases (four of nine tumours) demonstrated weak to moderate ER expression.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…[39][40][41][42] In their review of the literature, Garlick et al found that of the 44 cases of secretory carcinoma of the breast wherein IHC for hormone receptors were performed, eight of 44 (18%) of cases were ER positive, six of whom were men. 22 The group found no apparent association with ER positivity and age, tumour size, metastases or clinical outcome in these cases. In their immunohistochemical and genomic review of secretory carcinoma of the breast and mammary analogue secretory carcinoma, Krings et al reported 44% of their SCB cases (four of nine tumours) demonstrated weak to moderate ER expression.…”
Section: Discussionmentioning
confidence: 82%
“…In their review of the literature, Garlick et al . found that of the 44 cases of secretory carcinoma of the breast wherein IHC for hormone receptors were performed, eight of 44 (18%) of cases were ER positive, six of whom were men . The group found no apparent association with ER positivity and age, tumour size, metastases or clinical outcome in these cases.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the present case also, the tumor was located in the subareolar region which can be explained by the smaller relative size of the breast mound in younger patients deep to the nipple-areola complex. [15][16][17] Mammographic findings of SBC closely mimic a fibroadenoma as this carcinoma appears as a solitary, discrete lesion with a well-delineated margin. Since this carcinoma is more common in young girls, mammography always has diagnostic limitations because of the denser and glandular elements in the young breast.…”
Section: Discussionmentioning
confidence: 99%